Carbon nanomaterials staked with nonwoven (EG/PAN/CQDs) composite as a counter electrode for enhanced photons and photocatalytic efficiency - Syed, Noureen; Feng, Yongqiang; Fahad, Raja; Sahito, Iftikhar Ali; Huang, Jianfeng (Frontiers in Energy Research, 2023)
Prior studies on heavy metal heterojunction with carbon nanomaterials for dye-sensitized solar cells (D-SSCs) found that they were not only toxic but also had poor stability and led to a difficult synthesis. In this work, nanomaterials with flexible nonwoven sheets were employed to improve cell efficiency and were easily synthesized with high stability, durability, washability, and flexibility. By incorporating carbon quantum dots (CQDs) into the anode and counter electrodes, it is possible to boost photon efficiency by scattering the sunlight and turning a huge amount into current density. Here in this research, Textile carbon–based flexible dye-sensitized solar cells (TC-DSSC) with N-doped CQDs may significantly increase solar cell efficiency. Carbon-based nanoparticles stacked with textile apparel (nonwoven bamboo) sheets enabled the desired flexible end applications to be achieved. The prepared material significantly increased solar cell efficiency to 11.26% compared to 8.04% of the one without CQDs. Carbon-based nanomaterials are stacked with textile apparel (nonwoven bamboo) sheets to make them lightweight, highly flexible, wearable, and user-friendly. Furthermore, compared to pure expanded graphite on the nonwoven substrate, a single electrode incorporating CQDs offered low impedance and high current/voltage. On the other hand, when tested for photocatalytic activity using spectrophotometry, the proposed counter electrode made of expanded graphite, PAN, and CQDs loaded on nonwoven material completely degraded the methylene blue dye in a very short period of time. The N-CQDs may prove to be very stable with outstanding washing endurance anchored with expanded graphite layered on a nonwoven medium with an optimum thickness.